Deskripsi Pemahaman Konsep Matematis Mahasiswa Berdasarkan Teori APOS Dalam Perkuliahan Daring Materi Turunan: Description of Understanding Student Mathematical Concepts Based on APOS Theory in Online Lectures Derivative Material - Fitria, Mia; Yanti, Williza; Hidayat, Farid (Nusantara Journal of Education and Social Science, 2024)
Lectures conducted online still require students to be able to understand concepts with all existing limitations. The description of students' conceptual understanding carried out in this research uses Apos theory, namely action, process, object and scheme. The results of this research are expected to provide an overview or description of students' understanding of concepts based on APOS theory in derivative material. This research is descriptive research with a qualitative approach. The main instrument in this research is the researcher himself and the supporting instruments are test questions on derivative material and interview guidelines. The research subjects were students taking Mathematics courses from the Hospital Administration Study Program at STIKES Intan Martapura. The results of this research are that students who fulfill all APOS stages are in the high ability group of three people. None of the process and object stages were fulfilled by the low ability group. None of the scheme stages were fulfilled by the medium and low ability groups.